ECONOMIC SANCTIONS: THE ENTITY TYPES AND THEIR IMPACT ON THE FINANCIAL SUSTAINABILITY OF RUSSIAN ENTERPRISES - L. Milutina (Вестник университета, 2018)
This paper presents the historical aspect of economic sanctions and their types. Two-sided entity economic sanctions are reflected, on the one hand, as the measures, objectives and policy changes, on the other hand, the role of financial security. The effect on financial stability of Russian enterprises is traced, namely the indirect effect as well as the direct one. Positive trends and the negative consequences of economic sanctions in various branches of the Russian enterprises and in the economy as a whole are reflected.